Penggunaan Media Audio Visual terhadap Peningkatan Pengetahuan tentang Perilaku Hidup Bersih dan Sehat pada Anak Usia Sekolah - Sumi, Susi Sastika; Sugarni, Mika; Yusnaeni, Yusnaeni; Handayani, Wiwin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effect of using audio-visual media on increasing knowledge about clean and healthy living behavior in school-aged children. The method used is a quantitative research method with an experimental research type of one-group prepost design. The research sample consisted of 59 respondents using purposive sampling technique. The results of this study show that knowledge is in the good category after being given the intervention with an n value of 30, which means that 30 respondents experienced an increase in knowledge. And the sufficient value is n 2, which means there are 2 respondents with insufficient knowledge even though they have been given the intervention, and there are 27 respondents whose knowledge remains good or sufficient after being given the intervention. Based on the statistical output test, a significant value of 0.000 was obtained. This means that H0 is rejected because the significant value is <0.05 and Ha is accepted. The conclusion of this research is that there is an influence of the use of audio-visual media in increasing knowledge about clean and healthy living behavior in school-aged children Keywords: School age children, audio visuals, clean and healthy living behavior